2023
DOI: 10.1186/s40824-023-00374-x
|View full text |Cite
|
Sign up to set email alerts
|

Responsive manganese-based nanoplatform amplifying cGAS-STING activation for immunotherapy

Abstract: Background The activation of the cyclic guanosine monophosphate-adenosine monophosphate synthase-stimulator of interferon genes (cGAS-STING) signaling pathway has attracted great attention for its ability to up-regulate innate immune response and thus enhance cancer immunotherapy. However, many STING agonists limit the further advancement of immunotherapy due to weak tumor responsiveness or low activation efficiency. The responsive and effective activation of cGAS-STING signaling in tumors is a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Furthermore, various biosensors have also been designed using Mn-NSs. [2][3][4] In general, Mn is a part of the Earth's chemical composition and is the twelfth most abundant element. Manganese oxide is the most common form of Mn, and present in a broad range of environmental flora and fauna to control the biogeochemical elemental cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, various biosensors have also been designed using Mn-NSs. [2][3][4] In general, Mn is a part of the Earth's chemical composition and is the twelfth most abundant element. Manganese oxide is the most common form of Mn, and present in a broad range of environmental flora and fauna to control the biogeochemical elemental cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the cGAS-STING pathway can activate TIDCs, enabling them to effectively present tumor antigens and anti-inflammatory substances released during pyroptosis to T cells. , Therefore, simultaneous activation of the cGAS-STING pathway while inducing pyroptosis is expected to fully activate the immune pathway and amplify the adaptive immune response induced by pyroptosis. Among various cGAS-STING agonists, Mn 2+ has been shown to activate cGAS-STING signaling even in the absence of double-stranded DNA, thereby stimulating DC maturation . Consequently, Mn 2+ can be considered a propellant of the immune response to calcium overload mediated pyroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Among various cGAS-STING agonists, Mn 2+ has been shown to activate cGAS-STING signaling even in the absence of double-stranded DNA, thereby stimulating DC maturation. 27 Consequently, Mn 2+ can be considered a propellant of the immune response to calcium overload mediated pyroptosis. Moreover, H 2 Senhanced calcium pyroptosis can further amplify cGAS-STING activation by releasing mitochondrial DNA (mtDNA) as an adjuvant.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, pyroptosis is often accompanied by DNA damage, [ 7 , 9 ] including the production of double-stranded DNA (dsDNA). dsDNA can be detected by the cytoplasmic cGAS enzyme, leading to the conversion of adenylate triphosphate and guanosine triphosphate into 2’,3’-cyclic GMP-AMP and ultimately activating STING, resulting in the generation of type I interferons (especially IFN-β) and promoting the maturation of DCs [ 16 19 ]. Sun et al confirmed that Mn 2+ induces a hyperactivation of the cGAS-STING pathway, significantly enhancing the sensitivity of the cGAS enzyme to dsDNA [ 20 ].…”
Section: Introductionmentioning
confidence: 99%